British Prime Ministers and Democracy. - Quinault, Roland (Continuum International Pub. Group, 2011)
Today representative democracy is the dominant political system in the world. Britain played a prominent part in the democratization of the world through both its constitutional reforms at home and its power and influence abroad. In that process, Prime Ministers played a prominent role through their power and influence in government, Parliament and the country more generally. Quinault examines the stance of ten leading Prime Ministers - from the mid-nineteenth century until the twenty-first century - on the theory and practice of democracy. The attitude of each Prime Minister is assessed by co.